Penerapan Model Pembelajaran Think Pair Share Dalam Meningkatkan Keaktifan Dan Hasil Belajar Siswa Pada Materi Plantae Siswa Kelas X MIPA 3 Di SMAN 1 Belinyu - Deni Kurniawan; Indawan Indawan; Astrid Sri Wahyuni Suma (Universitas Hamzanwadi, 2025)
This study aims to improve students’ activeness and learning outcomes through the implementation of the cooperative learning model Think Pair Share (TPS) in the topic of Plantae for grade X MIPA 3 students at SMA Negeri 1 Belinyu. The background of this study lies in the low learning achievement, where only 33% of students reached the minimum mastery criterion (KKM) during online learning, as well as the lack of student engagement during teacher explanations. The research employed a Classroom Action Research (CAR) design based on Kurt Lewin’s model, consisting of four stages: planning, action, observation, and reflection, conducted in three cycles. The subjects were 37 students, and data were collected through achievement tests, observation of student activities, and documentation. The findings revealed a significant improvement in both student activeness and learning outcomes across the cycles. In terms of activeness, the indicator of task completion increased from 47% (cycle I) to 82% (cycle III), asking questions from 53% to 87%, and participating in discussions from 60% to 85%. Meanwhile, students’ learning outcomes also showed substantial progress, with classical mastery rising from 21.6% with an average score of 60 (cycle I), to 62.2% with an average of 75.9 (cycle II), and finally to 91.9% with an average of 85.7 (cycle III). It can be concluded that the implementation of the TPS learning model is effective in enhancing student activeness, collaboration, and learning outcomes in the topic of Plantae. These findings highlight the importance of cooperative learning strategies in fostering cognitive, affective, and psychomotor domains in the learning process.